The Use of Bacteriophages and Immunological Monitoring for the Treatment of a Case of Chronic Septicemic Cutaneous Ulcerative Disease in a Loggerhead Sea Turtle Caretta caretta. Issue 3 (2nd July 2021) - Greene, Whitney; Chan, Benjamin; Bromage, Erin; Grose, Julianne H.; Walsh, Cathy; Kortright, Kaitlyn; Forrest, Sue; Perry, Grace; Byrd, Lynne; Stamper, M. Andrew
Abstract: In this case study, phage therapy was applied to treat a multidrug‐resistant case of septicemic cutaneous ulcerative disease (SCUD) caused by Citrobacter freundii in a loggerhead sea turtle Caretta caretta . Phages were applied topically, intravenously, into the carapace, and into the exhibit water using various phage cocktails specific to the causative agent over an 8‐month period. This was performed in conjunction with antimicrobial therapy. The animal was monitored through weekly cultures, photographs, and complete blood cell counts, as well as immune assays (phagocytosis, plasma lysozyme and superoxide dismutase activity, and plasma electrophoresis profiles). The animal, in comparison to an untreated, unaffected control, had elevated antibody titers to the administered phages, which persisted for at least 35 weeks. Although cultures were clear of C. freundii after phage treatment, the infection did return over time and immune assays confirmed deficiencies when compared to a healthy loggerhead sea turtle. Immune parameters with statistically significant changes over the study period included the following: decreased phagocytosis, increased alpha‐ and gamma‐globulin protein components, and an increased albumin : globulin ratio. When C. freundii appeared again, the multidrug‐resistant status had reverted back to normal susceptibility patterns. Although not completely known whether it was another subspecies of bacteria, the therapy did resolve the multidrug‐resistant challenge. Phage therapy in combination with antimicrobial agents may be an effective treatment for sea turtles with normally functioning immune systems or less‐severe infections. Additional research is needed to better understand and quantify sea turtle immunology.